Analisis Risiko Usahatani Salak Organik di Desa Sibetan Kecamatan Bebandem Kabupaten Karangasem - I GUSTI AYU AGUNG DEWI MAHAYANI; I KETUT BUDI SUSRUSA; I WAYAN BUDIASA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
The Risk Analysis of Zallaca Organic Farming in Sibetan Village Subdistrict Bebandem Karangasem Regency Sibetan village is a development center of zallaca organic farming in subdistrict Bebandem, Karangasem regency. The problems that have been faced by zallaca organic farming like a fluctuation of production and commodity prices, thus indicating the risk that must be faced by the farmers related to production and the selling price of the commodity in the market. If production and price has a risk, it will affect to the farmers income. This study aimed to analyze factors that affect the income of farmers in zalacca organic farming, analyze the production risk, price risk and income with a risk. The research method used quantitative analysis.The result showed the factors that affect the farmers income of zallaca organic farming in Sibetan Village are the land area. The research shows the average farming costs incurred by Rp 2.784.050,78 farming per hectare, while the average total revenue obtained by Rp 9.493.215,20 per hectare, thus obtained the average income of zallaca organic by Rp 6.709.164,27 per hectare. The coefficient variation in production is 0,50 which means the production of zalacca organic in Sibetan village has a low risk, the value of the coefficient variation in price is 0,11, which means the price or organic zallaca commodity in Sibetan village has a low risk, and the coefficient variation income is 0,55 means that farm income zalacca organic at Sibetan village has a low risk.